Unraveling the dual threat: sarcopenia and insufficient physical activity in diabetes risk - Shi, Hui (Frontiers in Endocrinology, 2025)
PurposeThis study aimed to investigate the alterations in diabetes risk associated with sarcopenia and insufficient physical activity, as well as the demographic shifts within the diabetic population.MethodUtilizing pertinent data from the National Health and Nutrition Examination Survey (NHANES) database spanning 2011 to 2018, the criteria for sarcopenia were established by the Foundation for the National Institutes of Health. These criteria were calculated using lean body mass data in conjunction with body mass index data. Physical activity levels were assessed using the PAQ questionnaire from the NHANES database. The presence of diabetes was determined through the DIQ questionnaire and the laboratory examination within the NHANES database. The analysis was performed using multivariable logistic regression.ResultThe prevalence of both sarcopenia and insufficient physical activity in the diabetic population was 188% greater than in the non-diabetic population. Sarcopenia and insufficient physical activity were positively correlated with an increased risk of diabetes onset, demonstrating a 1.45-fold heightened risk when both conditions were present (OR=2.45,95%CI,1.35-4.44,P<0.05). This combined effect was significantly greater than the risk associated with sarcopenia alone (OR=1.84,95%CI,1.09-3.11,P<0.05) or insufficient physical activity alone (OR=1.55,95%CI,1.11-2.15,P<0.05).ConclusionA synergistic relationship exists between sarcopenia and insufficient physical activity, resulting in a markedly elevated risk of diabetes when both conditions are present concurrently. Therefore, comprehensive diabetes management strategies should prioritize populations exhibiting both sarcopenia and insufficient physical activity.